Influence of pulsed current arc welding to preclude the topological phases in the aerospace grade Alloy X. (April 2020) - Sathishkumar, M; Manikandan, M
Alloy X is prone to liquation and solidification cracks in the weldments, because of the development of topologically close-packed precipitates such as σ, P, M6 C, and M23 C6 carbides during arc welding methods. The present work examines the possibility of alleviating the segregation of Cr and Mo content to eliminate the development of topologically close-packed phases using a conventional arc welding technique. The welding of Alloy X has been achieved with ERNiCrMo-2 filler material by gas tungsten arc welding and pulsed current gas tungsten arc welding technique. The optical microscope shows the refined microstructure in pulsed current gas tungsten arc with respect to gas tungsten arc welding. The Mo-rich segregation was identified in gas tungsten arc weldment, and the same was absent in pulsed current gas tungsten arc. These segregations of Mo-rich content encourage the development of M3 C and M6 C secondary precipitates in gas tungsten arc welding. Pulsed current gas tungsten arc welding shows the existence of NiCrCoMo precipitate. The present work confirmed the absence of P, σ, and M23 C6 in both the weldments of Alloy X. The ultimate tensile strength, microhardness, and impact strength of pulsed current gas tungsten arc welding are increased by 3.39, 9.17, and 21.62%, respectively, with gas tungsten arc welding. The observed Mo-rich M3 C and M6 C secondary phases in the gas tungsten arc welding affect the tensile strength of the weldments.